Growth differentiation factor 15 ameliorates nonalcoholic steatohepatitis and related metabolic disorders in mice - Kim, Kook Hwan; Kim, Seong Hun; Han, Dai Hoon; Jo, Young Suk; Lee, Yong-ho; Lee, Myung-Shik (Scientific reports, 2018)
Growth differentiation factor 15 (GDF15) is an endocrine hormone belonging to the TGFβ superfamily member. GDF15 administration or GDF15 overexpression has been reported to have anti-obesity and anti-diabetic effects. Although non-alcoholic fatty liver disease (NAFLD)/non-alcoholic steatohepatitis (NASH) is frequently associated with obesity and insulin resistance, the functional role of endogenous GDF15 and therapeutic effect of GDF15 overexpression in NASH and related metabolic deterioration have not been evaluated. Here, we found that GDF15 expression was increased in the livers of NASH animal models and human subjects with NASH. Elevated expression of GDF15 was due to diet-induced hepatic endoplasmic reticulum (ER) stress. Gdf15 -knockout mice exhibited aggravated NASH phenotypes such as increased steatosis, hepatic inflammation, fibrosis, liver injury, and metabolic deterioration. Furthermore, GDF15 directly suppressed expression of fibrosis-related genes and osteopontin (OPN), contributing factors for NASH-related fibrosis, in hepatic stellate cells in vitro and in the liver of mice in vivo . Finally, we found that GDF15 -transgenic mice showed attenuation of NASH phenotypes and metabolic deterioration. Therefore, our results suggest that induction of endogenous GDF15 is a compensatory mechanism to protect against the progression of NASH and that GDF15 could be an attractive therapeutic candidate for treatment of NASH and NASH-related metabolic deterioration.